Cardiometabolic risk profile among children with migrant parents and role of parental education: the IDEFICS/I.Family cohort - Lindblad, Anna; Samkange-Zeeb, Florence; de Henauw, Stefaan; Solea, Antonia; Veidebaum, Toomas; Lauria, Fabio; Moreno, Luis A.; Iguacel, Isabel; Molnár, Dénes; Ahrens, Wolfgang; Winkler, Volker; Lissner, Lauren; et al. (International journal of obesity, 2023)
Evidence shows that migrant children have a higher risk of developing obesity than those with native parents. We aimed to investigate the association between parental migration background and cardiometabolic health in children and adolescents in Europe.
Gesehen am 26.02.2026